2020
DOI: 10.3389/fpubh.2020.00200
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Late Prematurity in the University Hospital of Valle Cali, Colombia During 2013–2014

Abstract: Introduction: The birth rate of late premature babies has been increasing in recent years, composing now 75% of all premature births. This growing trend can be explained by different demographic transformations such as an increase in the demand for infertility treatments, older maternal age and the higher incidence of multiple pregnancies, cesarean sections, and labor induction. These premature babies contribute 30% to the global neonatal mortality rate. Objective: To identify the factors associated with late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In particular, we focused on the predictive performance of the validated markers for late PTB. We noted that late preterm infants with an increased birth rate composed now 75% of all preterm infants [ 60 ]. It is still an important public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we focused on the predictive performance of the validated markers for late PTB. We noted that late preterm infants with an increased birth rate composed now 75% of all preterm infants [ 60 ]. It is still an important public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…When we evaluated the maternal variables by gestational age, we found that babies under 32 weeks have a three-fold risk of not having adequate prenatal care compared to those over 32 weeks. In 2013, a study conducted among late preterm infants in a public institution in Cali found that in 98% of the cases, the mothers had inadequate prenatal care (defined as fewer than three controls) (21). Another study in six low-and middle-income countries found that less than three prenatal controls increased the risk of premature birth by 1.68 times (16).…”
Section: Discussionmentioning
confidence: 99%